2010
DOI: 10.1136/pgmj.2009.090886
|View full text |Cite
|
Sign up to set email alerts
|

Tricuspid regurgitation: contemporary management of a neglected valvular lesion

Abstract: Right-sided cardiac valvular disease has traditionally been considered less clinically important than mitral or aortic valve pathology. However, detectable tricuspid regurgitation (TR) is common and recent data suggest that significant TR can lead to functional impairment and reduced survival, particularly in patients with concomitant left-sided valvular disease. The tricuspid valve is a complex anatomical structure and advances in three dimensional echocardiography and cardiac MRI have contributed to a greate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 49 publications
1
17
0
Order By: Relevance
“…Bernal et al believed that annuloplasty ring were more effective than De Vega procedure in preventing late TI after mitral valve repair for rheumatic heart disease. 18 Our study also demonstrated that ring annuloplasty had more efficacies in restoring and maintaining tricuspid valve function immediately after surgery and also in the long term, which indicates that ring annuloplasty is more durable method for TI repair.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…Bernal et al believed that annuloplasty ring were more effective than De Vega procedure in preventing late TI after mitral valve repair for rheumatic heart disease. 18 Our study also demonstrated that ring annuloplasty had more efficacies in restoring and maintaining tricuspid valve function immediately after surgery and also in the long term, which indicates that ring annuloplasty is more durable method for TI repair.…”
Section: Discussionsupporting
confidence: 66%
“…18 It has been shown that ring annuloplasty remodels the annulus, decreases tension on suture lines, increases leaflet cooptation, and prevents recurrent annular dilatation, all reasons to prefer prosthetic over simple suture annuloplasty in the presence of risk factors for tricuspid repair failure, such as significant right heart dilatation and dysfunction. [17][18][19][20] If the PASP is markedly increased or the annulus moderately dilated, relatively minor leaflet disease may lead to functional TI. [19][20][21] Rheumatic heart disease (RHD) patients tend to have poor right heart function even before the occurrence of functional TI therefore the correction of even mild or moderate TI in these patients necessitates a more stable and durable annuloplasty method.…”
Section: Discussionmentioning
confidence: 99%
“…Its results are diverse depending on the series, related in part to its complex anatomy and, to a greater extent, due to its lower incidence and experience and to the change in its approach through the therapeutic strategy in recent years [1,4].…”
Section: Case Reportmentioning
confidence: 99%
“…The latest studies on patients with tricuspid insufficiency secondary to left valve dysfunction, in whom surgical treatment of the tricuspid valve was not performed, show that in 60% of the cases there is no regression of the disease, which has made much more frequent the surgery on this valve affected as primary or secondary [1,4]. The perioperative mortality of this disease is high and is associated in a significant way with the patient's previous pathology, the cardiological status at the moment of the intervention, and the time of extracorporeal circulation and ischemia [2,6,11] (Figure 1).…”
Section: Case Reportmentioning
confidence: 99%
“…42 In the presence of severe right EMF, this assessment may be hampered by the absence of gradient across the tricuspid valve, by the presence of large right atrial thrombi deviating the regurgitant jet, or by major distortion of heart anatomy. 15 In such cases, pulmonary regurgitation may be used to estimate the mean and diastolic pulmonary pressures (Fig.…”
Section: Echocardiography and Dopplermentioning
confidence: 99%